Efectos de la suplementación con HMB sobre la composición corporal en ratas - de Araujo, Rafael Gavassa; Castoldi, Robson Chacon; Dos Santos, Carolina Cabral [UNESP]; Machado, Joao Henrique Lyrio [UNESP]; Ozaki, Guilherm Akio Tamura [UNESP]; Garcia, Thiago Alves [UNESP]; Teixerira, Giovana Rampazzo [UNESP]; Fihlo, Jose Carlos Silva Camargo [UNESP]; Papoti, Marcelo (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2017)
The aim was to investigate the effects of HMB supplementation on the physical performance and anthropometric parameters of Wistar rats that underwent eight weeks of concurrent training. We used 22 male Wistar rats of approximately 60 days of age, And were divided into four groups: control (C), supplemented control (SC), exercise (E) and supplemented exercise (SE). The training consisted of 30 minutes of swimming with an overload corresponding to 70 % of the anaerobic threshold, a one-minute interval, and four sets of ten jumps in water with a one minute interval between sets and a load of 50 % of body weight. After the tests, the tLIM and tTESTE were obtained and used to evaluate the performance of the animals, and anthropometric indices evaluated. The weight increases during the treatment in the SC animals was significantly higher than the animals in groups C and E. The absolute weight of the muscles, kidney and epididymal fat showed higher values for the SC and SE groups in relation to the others.
Effects of HMB supplementation on body composition of rats
Keywords: Anthropometic measures; Concurrent training; Performance; Wistar rats